2019
DOI: 10.1007/s10668-019-00319-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of neural networks and spatial interpolation to predict groundwater quality

Abstract: The artificial neural networks share its working analogous with the human brain; and by using these artificial neural models, various complex nonlinear relationships can be modeled which cannot be described easily using mathematical equations. In this study, groundwater quality at a sanitary landfill site used for solid waste disposal was modeled using artificial neural networks. The groundwater quality was assessed for two consecutive years 2016 and 2017 at ten locations near the site, and the data were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 23 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Surface water extraction, change detection and environmental assessment were prerequisites for water resources management [11]. Kalawapudi Komal used artificial neural network to model the groundwater quality of sanitary landfill for solid waste treatment in the research [12]. These studies showed that the application of BPNN had a positive effect, but there were still some problems.…”
Section: Prefacementioning
confidence: 99%
“…Surface water extraction, change detection and environmental assessment were prerequisites for water resources management [11]. Kalawapudi Komal used artificial neural network to model the groundwater quality of sanitary landfill for solid waste treatment in the research [12]. These studies showed that the application of BPNN had a positive effect, but there were still some problems.…”
Section: Prefacementioning
confidence: 99%
“…8 The dissolution of multivalent ions, such as Ca(II), Mg(II), Sr(II), Fe(II), and Mn(II), and their associated anions such as HCO 3 − , SO 4 2− , Cl − , NO 3 − , etc., from seepage, sedimentary rocks (such as chalk and limestone), and soil run-off causes water hardness. 9 Drinking hard water can lead to health issues such as cardiovascular diseases, dental difficulties, atopic eczema, and Alzheimer's disease, 5,10 as well as kidney diseases when associated with trace amounts of heavy metals and fluorides. 11 Heavy metal poisoning from drinking water is a global concern.…”
Section: Introductionmentioning
confidence: 99%
“…Few research studies (Yesilnacar et al 2008;Mohanty et al 2010;Sunayana et al 2019) suggest that neural network models could help in predicting the groundwater quality and groundwater level well in advance for understanding the future scenario. Artificial neural network (ANN) models have also been applied to the water quality problems by several researchers (Singh et al 2009;Ay and Kisi 2012;Csábrági et al 2017).…”
Section: Introductionmentioning
confidence: 99%